Grasses : Bromus to Paspalum, Second Edition - Mohlenbrock, Robert H., 1931- (Book collections on Project MUSE., 2002)
Since the publication of the first edition of Grasses: Bromus to Paspalum in 1972, twenty-two additional taxa of grasses have been discovered in Illinois that are properly placed in this volume. In addition, numerous nomenclatural changes have occurred for plants previously discovered, and many distributional records have been added. New keys have been prepared for each genus where additional species from Illinois are known. For new species, full-page illustrations are provided. This second edition updates the status of Illinois grasses. The book features 263 fig.